1998
DOI: 10.1021/jp983050n
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Kinetic Measurements of the Condensation and Evaporation of D2O Molecules on Ice at 140 K < T < 220 K

Abstract: The kinetics of condensation of D 2 18 O water vapor on D 2 16 O ice was studied in the temperature range 140-220 K. The measurements have been performed in real time using the pulsed valve technique in a lowpressure flow reactor. Ice samples were prepared by several different methods. The uptake coefficient γ was observed to decrease with increasing surface temperature, and varied from γ ) 0.06 to 0.8. A significant dependence of γ on the method of preparation of the ice has been found. At 180 K, γ ) 0.13 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 37 publications
10
66
2
Order By: Relevance
“…The value of the uptake coefficient of water on ice is an area of active debate with evidence suggesting that α w < 1 (Chaix et al, 1998;Marek and Straub, 2001;Pratte et al, 2006;Davidovits et al, 2006). However, for pure ice surfaces at our ms experimental timescales we observe complete trapping of water molecules, and therefore assume α w = 1 for consistency, and to calculate an upper bound for α b (T ).…”
Section: Discussionmentioning
confidence: 75%
“…The value of the uptake coefficient of water on ice is an area of active debate with evidence suggesting that α w < 1 (Chaix et al, 1998;Marek and Straub, 2001;Pratte et al, 2006;Davidovits et al, 2006). However, for pure ice surfaces at our ms experimental timescales we observe complete trapping of water molecules, and therefore assume α w = 1 for consistency, and to calculate an upper bound for α b (T ).…”
Section: Discussionmentioning
confidence: 75%
“…These two are closely related by ⌬H sub ϭ E des Ϫ E ads where E ads is the energy barrier to adsorption. For ice films, E ads is very small below 200 K, and ⌬H sub Х E des [33]. The same condition is likely to hold true for the nitric acid hydrate films.…”
Section: Discussionmentioning
confidence: 79%
“…We assume that the same holds true for the other films in this study. A recent study [33] reported a negative effective activation barrier to ice adsorption of around Ϫ0.3 kcal/mol below 200 K for ice that has been condensed from vapor. At higher temperatures, they do report a significant, Ϫ4.2 Ϯ 1 kcal/mol barrier to ice adsorption with a concomitant decrease in the activation barrier to evaporation.…”
Section: Zero-order Desorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many atmospheric applications, the uncertainty in the vapour pressure of ice is small compared to other uncertainties. For example, there is a range exceeding a factor of ten in estimates of the uptake coefficient of water vapour on ice at 200 K (Chaix et al 1998). This uncertainty propagates into computer models of cirrus clouds (Lin et al 2002;Gierens et al 2003).…”
Section: Conclusion and Future Needsmentioning
confidence: 99%